Promoting Infrastructure Development in Brazil - Mourougane, Annabelle (OECD Economics Department Working Papers, 2011)
Brazil under-invested in infrastructure for over three decades, and infrastructure investment rates have come up only slowly since 2007. Infrastructure needs are sizeable in almost all sectors. It is likely that at its current stage of development the country will benefit from large pay-offs from infrastructure spending. Against this background, the Brazilian authorities have put in place a large infrastructure plan named Growth Acceleration Programme (Programa de aceleração do crescimento, PAC). This programme has been rightly protected from the fiscal cuts announced in early 2011. Nevertheless, some changes to the policy and regulatory framework could be introduced to make public investment more cost-efficient and to foster private participation. In particular: • The second stage of PAC needs to focus on completing the most worthwhile programmes. In addition, the public-private partnership framework should be streamlined.